(untitled) (Zaporizhzhia Historical Review, 2021)
In given article the author makes an attempt to analyse first steps of German ethnos of Ukraine on national not state formations creation on the territory of this country. The conclusion, that this problem is done, without taking into account empirical material, is still insufficiently studied in a native historiography.